Parents in Choosing Motivation Viewed from ECD Profile Educational Institutions - Saputri, Endang Dwi; Tasuah, Neneng (BELIA: Early Childhood Education Papers, 2017)
Parental awareness about the importance of education from an early age is increasing. As time, a parent is required to be a parent today should have a specific strategy for the future of their children. This is evidenced by the amount of attention given to the selection of childrens education. In terms of selecting parent education see specific criteria. This research uses descriptive qualitative research method. The informant sources of primary data in this study are: Chief TK Kemala Bhayangkari 85 Kebumen and parents, Head of IT Ulil Albab Kebumen kindergarten and kindergarten students parents as well as State Trustees and Parents. The collection of data through interviews, questionnaires, observation and documentation. Data analysis included, data collection, data reduction, data presentation and conclusion. The results of this study indicate that the motivation of parents in choosing ECD at three institutions, appeared with the reasons vary, in kindergarten Kemala Bhayangkari motivation of parents come together with an awareness of the importance of early childhood education, school quality was good, school fees affordable, location close to home and easy access, as well as young police uniform as a special attraction. TK IT Ulil Albab, parental motivation occurs because the predicate and school achievement, faith-based education, childs comfort, service provided by the agency to the child and the parents in the form of commucation intertwined easy and open. Motivation parents choose TK Negeri Pembina State is the predicate, the location is in the city center, the resulting output as well as extracurricular drumband. And a unique and characteristic as an attraction to the public. TK Kemala Bhayangkari 85 with little police uniforms and marching band activities, TK IT Ulil Albab with the peculiarities of his religious training and TK Negeri Pembina Kebumen with domestic status and output. Which indirectly may attract the attention of parents and children, so that in the end they decided to choose the institution.